Impulse control disorder in PD: A lateralized monoaminergic frontostriatal disconnection syndrome?. (September 2016) - Premi, E.; Pilotto, A.; Garibotto, V.; Bigni, B.; Turrone, R.; Alberici, A.; Cottini, E.; Poli, L.; Bianchi, M.; Formenti, A.; Cosseddu, M.; Gazzina, S.; et al.
Abstract: Background: Impulse Control Disorder symptoms (ICD) in Parkinson's disease (PD) has been recently associated by magnetic Resonance imaging with impaired cortico-striatal connectivity, especially between left putamen and frontal associative areas. Methods: 84 patients entered the study (21 PD-ICD+ and 64 PD-ICD-) and underwent DATSCAN imaging. The striatal tracer uptake was evaluated using BRASS software (Hermes, Sweden). The whole-brain analysis was performed with Statistical Parametric Mapping (SPM). Results: PD-ICD+ showed a significant reduction of left putaminal and left inferior frontal gyrus tracer uptake compared to PD-ICD-. Functional covariance analysis using left putamen as the seed point showed that, in contrast to ICD-patients, ICD+ patients had no functional covariance with contralateral basal ganglia and ipsilateral cingulate cortex, as index of an impaired inter- and intra-hemispheric dopamine binding in PD-ICD+. Discussion: the results support and expand the concept of a functional disconnection syndrome linked to ICD symptoms in PD patients through an asymmetric molecular frontostriatal network breakdown with left basal ganglia as central hub. Highlights: We studied Impulse Control Disorder (ICD) in Parkinson's disease. We evaluated striatal and extrastriatal DATSCAN uptake. PD-ICD + showed a significant reduction in left putamen and left inferior frontal gyrus. Impairment of inter- and intra-hemispheric binding in PD-ICD + patients was evident. Left basal ganglia was key in an asymmetric molecular frontostriatal network breakdown.